Primary Hyperparathyroidism Caused by Single Parathyroid Adenoma - Jose R. L. Batubara; Paruhum T. Siregar; M. Lutfi; Daniel Makes; Wawan Hermawan (Indonesian Pediatric Society, 1995)
Primary hyperparathyroidism is rarely found in children under sixteen years old. We report the first case seen at the Department of Child Health, Medical School, University of Indonesia, Jakarta. This 15-year old girl was admitted to the Department, referred by an orthopedic surgeon because of pathologic fractures suspected to be caused by hyperparathyroidism. The physical examination was unremarkable, and the laboratory findings showed increased level of parathyroid hormone. Roentgenologic examination showed lytic skull lesions, loss of the lamina dura of the dentis, subperiosteal resorption of the symphysis and generalized osteoporosis with pathologic fractures. Color Doppler USG using a high resolution ultrasound examination was performed to find the etiology of primary hyperparathyroidism. The result revealed single parathyroid adenoma in the right superior region measuring 2.7 x 1.7 x 1 cm. The clinical manifestation and laboratory findings showed improvement following surgery.